Economic Life of Traders in Bauntung Market, Banjarbaru City 1999-2021 - Rahmatika, Alliya; Effendi, Rusdi; Mardiani, Fitri (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to find out the economic life of traders in Bauntung market, Banjarbaru city. The research method used a historical method consisting of heuristics, criticism, interpretation, and historiography. The results showed that Bauntung market was established in 1965 designed by Van Der Pijl and built in a residential area, with a movie theater behind it. In 1999-2012 Bauntung market was the main center of trade without any competition from modern markets. However, along with population growth and technological development, competition from modern shopping centers began to emerge, which affected the stability of merchants' income. Furthermore, in 2020-2021 the economic life of traders was faced with the Covid-19 pandemic and plus 2021 the market was relocated which led to a reduction in the number of customers and a decrease in income.